Implementasi Algoritma Rough Set Untuk Memprediksi Jumlah Pendaftar Siswa Baru Pada SMK Swasta Sinar Harapan - Novianti, Sinta; Hasugian, Paska Marto (Jurnal Teknik Informatika UNIKA Santo Thomas, 2021)
ABSTRACT Where the number of new student registrants at the Sinar Harapan Private Vocational School is unstable every year and the school has difficulty predicting how many new student registrants will be in the coming year and preparing extracurricular activities such as English/computer training or the best facilities for new students such as chairs, tables, classrooms and so on, as well as the competitiveness of private schools in the district. banyan. So we need a system that can dig up data and help predict the number of new student registrants, using data mining techniques, namely the Rough Set Algorithm which aims to get a short rule estimate from a table, in this study using student registration data in 2018, 2019, 2020. By applying data mining with the rough set algorithm and carrying out the rough set stages, it can produce decisions in the form of generating rules (knowledge), and the results of the calculation analysis are 152 students to predict the number of students in the coming year.